ECOLOGICAL, PHYSIOLOGICAL, GENETIC TRADE-OFFS AND SOCIO-ECONOMIC IMPLICATIONS OF TROPHY HUNTING AS A CONSERVATION TOOL: A NARRATIVE REVIEW - Victor K. Muposhi1; Edson Gandiwa; Stanley M. Makuza; Paul Bartels (Journal of Animal and Plant Sciences, 2017)
Although the contribution of trophy hunting as a conservation tool is widely recognised, there is perpetual debate and polarization on its sustainability. This review integrates five themes mostly considered in isolation, as independent research fields in wildlife conservation: (1) trophy quality and population ecology of hunted species, (2) behavioural ecology of hunted populations and associated avoidance mechanisms, (3) physiological stress in hunted populations, (4) genetic variability and desirable traits, and (5) socio-economic imperatives in wildlife conservation. We searched for articles on search engines using specific key words and found 350 articles from which 175 were used for this review under five key themes. Population and trophy quality trends of commonly hunted species seem to be declining in some countries. Elevated hunting pressure is reported to influence the flight and foraging behaviour of wildlife thus compromising fitness of hunted species. Selective harvesting through trophy hunted is attributed to the decline in desirable phenotypic traits and increased physiological stress in most hunted species. Though it provides financial resources need for conservation in some countries, trophy hunting works well in areas where animal populations are healthy and not threatened by illegal harvesting and other disturbances. There remains much polarity on the sustainability of trophy hunting in modern-day conservation. More research need to be conducted across the five themes examined in this review for broader analytical analysis and comparison purposes. A new research agenda is needed regarding wildlife sustainable use principles and their sustainability and acceptability in modern-day conservation.
Keywords: Wildlife harvesting; wildlife behaviour; landscape of fear; conservation physiology; genetic diversity; trophy hunting bans